Effects of social distancing policy on labor market outcomes. (11th September 2022) - Gupta, Sumedha; Montenovo, Laura; Nguyen, Thuy; Lozano‐Rojas, Felipe; Schmutte, Ian; Simon, Kosali; Weinberg, Bruce A.; Wing, Coady
Abstract: US workers receive unemployment benefits if they lose their job, but not for reduced working hours. In alignment with the benefits incentives, we find that the labor market responded to COVID‐19 and related closure‐policies mostly on the extensive (12 pp outright job loss) margin. Exploiting timing variation in state closure‐policies, difference‐in‐differences (DiD) estimates show, between March 12 and April 12, 2020, employment rate fell by 1.7 pp for every 10 extra days of state stay‐at‐home orders (SAH), with little effect on hours worked/earnings among those employed. Forty percentage of the unemployment was due to a nationwide shock, rest due to social‐distancing policies, particularly among "non‐essential" workers.